FAKTOR RISIKO KEJADIAN CARPAL TUNNEL SYNDROME (CTS) PADA PEKERJAAN PENGGUNA KOMPUTER : LITERATURE REVIEW - Dinda Adharia Ghaisani; Siswi Jayanti; Ekawati Ekawati (Jurnal Kesehatan Masyarakat (Undip), 2021)
Working using computers has a risk of developing Carpal Tunnel Syndrome due to repetitive movements of the hands and fingers for a long time. If the activity takes place in an odd and long-time position, it will cause muscle weakness in the worker's hands. This study aimed to analyze the risk factors for the occurrence of CTS towards computer users workers. The method used in this research was literature review comparative study. The articles used were obtained online through several trusted non-print journal sites such as Scopus, PubMed, Science Direct and Google Scholar in the last 10 years (2010-2020). The literature review research was conducted on 15 articles consisting of 9 national articles and 6 international articles. Articles are analyzed through stages of editing, organizing, analyzing, and then disseminating. The results of this study indicate that individual factors, including age, gender, body mass index, history of disease and years of service, as well as occupational factors, including length of work, repetitive movements, and awkward posture, are related to the occurrence of CTS in computer users. Individual factors that has a strongly associated with the incidence of CTS is years of service. While the work factor that has a strongly associated with the incidence of CTS was the odd work posture on the hands